1999
DOI: 10.1136/hrt.82.6.668
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine echocardiography predicts functional outcome after revascularisation in patients with dysfunctional myocardium irrespective of the perfusion pattern on resting thallium-201 imaging

Abstract: Objective-To evaluate whether the predictive value of dobutamine echocardiography for assessing contractile reserve was altered by diVering patterns of regional myocardial perfusion. Patients-31 consecutive patients with symptomatic congestive heart failure (left ventricular ejection fraction < 35%) caused by coronary artery disease. Setting-A district general hospital. Methods-Thallium-201 perfusion imaging and low dose dobutamine (5-15 µg/kg/ min) echocardiography were performed and resting echocardiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…However, it has also been suggested that where there is a severely compromised coronary flow reserve, it is likely that stimulation of the myocardium by even low doses of dobutamine may precipitate myocardial ischemia by increasing the oxygen demand beyond the already compromised threshold [39]. In a study from our institute involving 31 patients with a predominant history of heart failure and severe left ventricular dysfunction (LVEF = 25% 69%), 39% of the severely dysfunctional segments showed normal perfusion, 32 showed moderately reduced perfusion, and 29% were severely underperfused [41]. Contractile response during dobutamine was similar in the normally perfused and moderately underperfused dysfunctional segments (Fig.…”
Section: Dobutamine Echocardiographymentioning
confidence: 96%
See 3 more Smart Citations
“…However, it has also been suggested that where there is a severely compromised coronary flow reserve, it is likely that stimulation of the myocardium by even low doses of dobutamine may precipitate myocardial ischemia by increasing the oxygen demand beyond the already compromised threshold [39]. In a study from our institute involving 31 patients with a predominant history of heart failure and severe left ventricular dysfunction (LVEF = 25% 69%), 39% of the severely dysfunctional segments showed normal perfusion, 32 showed moderately reduced perfusion, and 29% were severely underperfused [41]. Contractile response during dobutamine was similar in the normally perfused and moderately underperfused dysfunctional segments (Fig.…”
Section: Dobutamine Echocardiographymentioning
confidence: 96%
“…Although fatty acid oxidation is preserved in hibernating myocardium [23], the clinical results with these tracers have not been encouraging [24]. 11 C-acetate has, however, been used successfully [25]. Uptake of this tracer depends upon myocardial perfusion and its clearance from the myocardium is a measure of oxidative metabolism.…”
Section: Imaging Techniques For Myocardial Viabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Contractile reserve, which is a marker of myocardial viability, may be assessed by low-dose dobutamine echocardiography or cardiac MRI [45][46][47][48][49]. Lately, gadolinium-based contrast agents with cardiovascular magnetic resonance (CMR) are used to assess late hyperenhancement of the myocardium, which reflects myocardial necrosis [50,51].…”
Section: Comparison Of Myocardial Contrast Echocardiography With Othementioning
confidence: 99%